The logic of the spirit in human thought and experience : exploring the vision of James E. Loder Jr. - Wright, Dana R.; White, Keith J. (Lutterworth Press, 2015)
In March 2012 a small consultation convened on the campus of Princeton Theological Seminary, where James E. Loder Jr. had served for forty years as the Mary D. Synnott Professor of the Philosophy of Christian Education. Members from the Child Theology Movement had begun to read Loder's work and they wanted to go further. So they invited former students of Loder's to meet with them for conversations about things that really mattered to them and to Loder: human beings (and especially children), the church's witness to the gospel of Jesus Christ, and discerning the work of Spiritus Creator in the.